Assessment of Community Pharmacists’ Knowledge, Perception and Practice Regarding Antimicrobial Stewardship in Ebonyi State, Southeastern Nigeria (African Journal of Biomedical Research, 2024)
Antimicrobial stewardship (AMS) is vital for promoting the appropriate use of antimicrobials. This study evaluated the knowledge, perception, and practice of community pharmacists regarding AMS in a Nigerian state. The cross-sectional study was conducted among community pharmacists using a 33-item structured questionnaire. Data collected were analyzed using the IBM SPSS Version 25.0, with significance level set as P < 0.05. Out of 79 distributed questionnaires, 70 were completed (participation rate: 88.6%). Majority of the respondents were males (n = 48, 68.6%), aged 26 – 45 years (n = 51, 72.9%), and had ≤ 10 years of community pharmacy experience (n = 54, 77.1%). Overall, more than half of the respondents possessed good AMS knowledge (n = 51, 72.9%), while approximately half had a positive perception (n = 38, 54.3%) and practiced AMS effectively (n = 36, 51.4%). Male pharmacists showed higher awareness of AMS compared to females (89.6% vs. 63.6%; ꭓ2 = 6.716, p = 0.010). Respondents who were Fellows of the West African Postgraduate College of Pharmacists (FPCPharm) had better AMS knowledge (100.0% vs. 67.8%; ꭓ2 = 4.862, p = 0.027) and a more positive perception (81.8% vs. 49.2%; ꭓ2 = 3.986, p = 0.046). While community pharmacists displayed good AMS knowledge, their perception and practice were average. Participation in the West African Postgraduate College of Pharmacists programme was associated with improved knowledge and perception of AMS. Strengthening inter-professional collaborations can optimize health outcomes. Enhancing antibiotic stewardship among Nigerian community pharmacists is imperative.